Hematological And Biochemical Blood Changes In Chronic Tendinitis Thoroughbred Race Horses (International Journal of Scientific Research and Management (IJSRM), 2020)
Tendon injury is the most important veterinary reason for wastage of thoroughbred racehorses. Clinical diagnosis of tendon injuries is confirmed by a combination of clinical, ultrasonographic or post mortem examination of the injured limb. In addition, measurement of hematological and biochemical blood parameters are an important tool that aid health assessment and decision-making in diagnosis, treatment and follow-up of the injured tendon. Therefore, the lack of information or misinterpretation of these parameters may affect the accuracy of disease diagnosis and then lead to poor treatment. The present study was conducted to evaluate the levels of some hematological and biochemical parameter in the blood of thoroughbred horses affected by chronic tendinitis and compared with normal horses. Blood samples were collected from 15 healthy thoroughbred horses (8 stallions and 7 mares) and 21 tendinitis thoroughbred horses (11 stallions and 10 mares); and the levels of 18 blood parameters were determined. The tendinitis horses had higher number of erythrocytes and thrombocytes, higher values of packed cell volume (PCV) and mean corpuscular volume (MCV); lower enzyme activity of creatine kinase (CK), lower values of lactic acid (LA), icteric index and mean corpuscular hemoglobin concentration (MCHC) and lower numbers of band neutrophils than the normal horses. The chronic tendinitis mares had higher number of thrombocytes and lower values of lactate dehydrogenase (LDH) enzyme activity, lactic acid, plasma proteins, MCHC and lower numbers of white blood cells (WBC) than the normal mares. The chronic tendinitis stallions had higher levels of lactic acid, plasma proteins, MCV, and higher numbers of erythrocytes and thrombocytes,; and lower values of icteric jaundice, MCHC, band neutrophils than the normal horses. No significant differences were reported when tendinitis mares were compared with tendinitis males. However, normal mares showed higher levels of plasma proteins than normal stallions. The results obtained by this study can be used as useful index to diagnose and treat chronic tendinitis in horses.